Wakaf Saham Sebagai Alternatif Wakaf Produktif Pada Perkembangan Ekonomi Syariah di Indonesia (TAWAZUN: Journal of Sharia Economic Law, 2020)
Sharia economic development has been introduced to various types of halal investments including sharia stocks. The development of Sharia stock exchanges is very rapidly growing in line with the ease of access to become Sharia equity investors. The purpose of this journal is to introduce the Waqf of shares and its application in the development of sharia economy. This research uses literature research where all the materials are sourced from various sources, such as books, journals, scientific papers, newspapers, online news, etc. that support the writing of this journal. The result of this journal is the new stock Waqf was introduced in April 2019, investors can have their shares personally or through AB-SOTS (the Exchange member who owns the Sharia Online Trading System) which is a securities company that owns SOTS, a securities company in cooperation with the Indonesian Waqf Agency (BWI) and Dompet Dhuafa (DD Currently the new MNC Sekuritas, Indopremier Securities, Henan Securities and Philip Sekuritas. Waqf shares as an alternative of waqf productive with the purpose of the welfare of the people.